2019
DOI: 10.1186/s12951-019-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

G2-S16 dendrimer microbicide does not interfere with the vaginal immune system

Abstract: It is essential that prophylactic drugs do not interfere with the normal function of the immune system. The use of nanoparticles as vaginal microbicides is a promising prevention strategy against sexually transmitted infections. With that aim, our group is working with the G2-S16, a second generation carbosilane dendrimer with sulfonate groups in the periphery, which has been previously shown to be effective against HIV-1 and HSV-2 infection, and it is now on the road to clinical trials. Our objective in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…98 No vaginal irritation was detected in BALB/c mice and female rabbits after various consecutive applications for different times with 3% G2-S16. 99 Daily treatment with G2-S16 either, by vaginal topical application or intravenous injection, does not modify the hemogram after 7 or 14 days of treatment. Interestingly enough, G2-S16 dendrimer does not interfere with the vaginal immune system.…”
Section: Nanocarriers or Drugsmentioning
confidence: 94%
“…98 No vaginal irritation was detected in BALB/c mice and female rabbits after various consecutive applications for different times with 3% G2-S16. 99 Daily treatment with G2-S16 either, by vaginal topical application or intravenous injection, does not modify the hemogram after 7 or 14 days of treatment. Interestingly enough, G2-S16 dendrimer does not interfere with the vaginal immune system.…”
Section: Nanocarriers or Drugsmentioning
confidence: 94%
“…Moreover, we performed several assays to investigate the impact of G2-S16 PCD in the vagina immune system. Our results demonstrated the biosafety of this G2-S16 PCD microbicide, as it did not modify the normal activity of the main immune system cells [ 75 ].…”
Section: How Does G2-s16 Pcd Work In Vitro?mentioning
confidence: 84%
“…In vitro G2-S16 PCD dendrimer microbicide does not interfere with the vaginal immune system. [75] 2020…”
mentioning
confidence: 99%
“…In addition to its unquestionable microbicidal effect, it has demonstrated in vivo biocompatibility. Recent studies showed that G2-S16 dendrimer does not cause irritation or inflammation in the vaginal epithelium and does not alter the natural immunity of the vagina, which strongly supports the biosafety of this dendrimer for vaginal application to control viral transmission [ 60 , 61 , 62 ].…”
Section: Nanotechnology Approaches For Prevention Of Hiv Infectionmentioning
confidence: 89%